Attitudes and Behaviours of Italian 3D Prosumer in the era of Additive Manufacturing - Bravi, Laura (2017)
The Additive Manufacturing technology can move the method of customization away from the conventional means; this technology can serve consumers as individuals in the same way craft customization can, but employing different forms of communication and interaction. The traditional consumer is changing his role, becoming at the same time producer and consumer of what he need. Therefore this research try to investigate how much this new trend in consumer attitudes is influencing Italian consumers, analyzing consumer knowledge and perception of 3D printing and their propensity to use these manufacturing technologies. The results show that in the Italian context although these technologies are known and appreciate from a third of the population, there is still ample room for growth in the use of Additive Manufacturing as innovative production tool of collaboration between companies and consumers.